Investigation Of Drug Nutrient Interactions And Physicochemical Compatibilities Of Ceftazidime, Cefotaxime And Cefepime In Neonatal Total Nutrient Admixtures Using HPLC - Iqbal, Muhammad Shahid (2013)
Total nutrient admixtures (TNAs) is widely used therapeutic intervention in the management of malnourished patients receiving parenteral nutrition since the approval of admixing intravenous fat emulsions with various amino acids and dextrose solutions. The advantages of TNAs include home nutrition therapy, less risk of infections, less need of nursing staff, no need of additional fluids to dilute the drugs, decreased administration costs compared with the conventional piggyback method and increased tolerance of intravenous fat emulsions in neonates. Addition of antibiotics to the TNAs often raises question of stability of the antibiotics over longer periods e.g. 24 hours. Unfortunately, very little data about TNAs stability in/with antibiotics is available. This study was aimed to evaluate the stability and compatibility of antibiotics (ceftazidime, cefepime and cefotaxime) in TNAs. The stability and compatibility were measured chemically, by using a high-speed HPLC (Prominence UFLC model LC-20AD, Shimadzu, Columbia, USA) based on newly developed and validated methods. Shelf life and percentage of remaining antibiotics in all formulations were measured at different time intervals (H0, H4, H8, H16 and H24) by using the above methods. The concentrations of TNAs’ components i.e. macronutrients and micronutrients used in the study were according to the normal body weight of neonates i.e. 3 kg neonates. The study evaluated the effect of varied concentrations of macronutrients in/with antibiotics. For each antibiotic, forty-eight TNAs formulations were prepared in different combinations of macronutrients (dextrose, amino acids and fats) and micronutrients (vitamins, xxvii and trace elements).